Pengujian Usability dengan Teknik System Usability Scale pada Test Engine Try Out Sertifikasi - Suyanto Suyanto; Usman Ependi (MATRIK : Jurnal Manajemen, Teknik Informatika dan Rekayasa Komputer, 2019)
Test engine try out is an information system used by prospective alumni students to practice the questions in taking the certification exams at Bina Darma University. Exercises that can be done on this test engine are vendor certifications such as Microsoft Technology Associate, SAP, NIIT, PASAS, CISCO, and various other certifications. To ascertain whether the test engine is in line with the expectations and needs of the participants try out then an evaluation is carried out. The evaluation technique used is usability with the system usability scale approach. System usability scale is an information system evaluation technique that looks at three aspects, namely adjective rating, grade scale, acceptability by involving end users in the evaluation process. In the process of evaluating the usability scale system, ten instruments were used as a measure of evaluation. From the evaluation, the final result is 87.33. According to these conditions, it can be concluded that the test engine try out from the side of the adjective rating includes the excellence group, from the grade scale side including B group, and from the acceptability side including the acceptable group.